Characterization of peanut (Arachis hypogaea) bandi - Seguera, Charisse Marie Occeña (2008.)
Characterization of peanut bandi using muscovado sugar, refined sugar and washed sugar by means of proximate composition, physico-chemical analyses and sensorial evaluation was assessed.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Peanut; Bandi